The Deviation Translate of Dutch Translation of the Quran â€œDe Deilige Qoer-anâ€ - Astari, Rika; Yusroh, Yusroh; Faturrahman, Muhammad Irfan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The Al-Quran translated by De Heilige Qoer-an (DHQ) was a translation of the Qur'an from The Holy Quran, by Maulana Muhammad Ali, the leader and founder of the Ahmadiyya Lahore. The translation of prophetic and miraculous verses shows the occurrence of translation deviations.. This article aims to show the forms of deviations in the translation and interpretation of De Heilige Qoer-an, the factors and the impact of deviations in translation on the context of the meaning of the Qur'an. Material object: in the form of translations of prophetic verses and miraculous verses from the Dutch translation of the Qur'an De Heilige Qoer-an. This research has used a qualitative descriptive approach. The method of data collection is by identifying prophetic verses and miracles of the apostles. Identification is done by comparing the Dutch translation of the Koran with the Indonesian translation of the Koran by H. Fachruddin HS H. Zainuddin Hamidy (1962). Content analysis has been used for data analysis. The translation deviation in DHQ is more caused by lexical translation and the ideology of the translator who translates the Qur'an rationally. The translation of the Qur'anic text based on the translator's ideology has shown a contrast in meaning with the text that corroborates the events of the prophets. ThestudyÂ provided a new point of view in looking at deviations in the translation of the Qur'anic text, because the existence of text references in other holy books can be a factor causing translation deviations.Ø§Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„Ø°ÙŠ ÙƒØ§Ù† ØªØ±Ø¬Ù…ØªÙ‡ Ø¨ De Heilige Qoer-an (DHQ) Ù‡Ùˆ ØªØ±Ø¬Ù…Ø© Ù„Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„ÙƒØ±ÙŠÙ… Ø§Ù„Ø°ÙŠ ÙƒØªØ¨Ù‡ Ù…ÙˆÙ„Ø§Ù†Ø§ Ù…ØÙ…Ø¯ Ø¹Ù„ÙŠØŒ Ø²Ø¹ÙŠÙ… ÙˆÙ…Ø¤Ø³Ø³ Ø§Ù„Ø£ØÙ…Ø¯ÙŠØ© Ù„Ø§Ù‡ÙˆØ±. ØªØ¸Ù‡Ø± ØªØ±Ø¬Ù…Ø© Ø§Ù„Ø¢ÙŠØ§Øª Ø§Ù„Ù†Ø¨ÙˆÙŠØ© ÙˆØ§Ù„Ù…Ø¹Ø¬Ø²ÙŠØ© ØØ¯ÙˆØ« Ø§Ù†ØØ±Ø§ÙØ§Øª ÙÙŠ Ø§Ù„ØªØ±Ø¬Ù…Ø©. ØªÙ‡Ø¯Ù Ù‡Ø°Ù‡ Ø§Ù„Ù…Ù‚Ø§Ù„Ø© Ø¥Ù„Ù‰ Ø¥Ø¸Ù‡Ø§Ø± Ø£Ø´ÙƒØ§Ù„ Ø§Ù„Ø§Ù†ØØ±Ø§ÙØ§Øª ÙÙŠ ØªØ±Ø¬Ù…Ø© ÙˆØªÙØ³ÙŠØ±DHQ ØŒ ÙˆØ¹ÙˆØ§Ù…Ù„ ÙˆØªØ£Ø«ÙŠØ± Ø§Ù„Ø§Ù†ØØ±Ø§ÙØ§Øª ÙÙŠ Ø§Ù„ØªØ±Ø¬Ù…Ø© Ø¹Ù„Ù‰ Ø³ÙŠØ§Ù‚ ØªØ±Ø¬Ù…Ø© Ù…Ø¹Ù†Ù‰ Ø§Ù„Ù‚Ø±Ø¢Ù†. Ù…Ø§Ø¯Ø© Ø§Ù„Ø¨ØØ«: ÙÙŠ Ø´ÙƒÙ„ ØªØ±Ø¬Ù…Ø§Øª Ù„Ù„Ø¢ÙŠØ§Øª Ø§Ù„Ù†Ø¨ÙˆÙŠØ© ÙˆØ§Ù„Ø¢ÙŠØ§Øª Ø§Ù„Ø¥Ø¹Ø¬Ø§Ø²ÙŠØ© Ù…Ù† Ø§Ù„ØªØ±Ø¬Ù…Ø© Ø§Ù„Ù‡ÙˆÙ„Ù†Ø¯ÙŠØ© Ù„Ù„Ù‚Ø±Ø¢Ù† DHQØŒ Ø§Ø³ØªØ®Ø¯Ù… Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ÙˆØµÙÙŠ Ø§Ù„Ù†ÙˆØ¹ÙŠ. Ø·Ø±ÙŠÙ‚Ø© Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ù‡ÙŠ ØªØØ¯ÙŠØ¯ Ø§Ù„Ø¢ÙŠØ§Øª Ø§Ù„Ù†Ø¨ÙˆÙŠØ© ÙˆÙ…Ø¹Ø¬Ø²Ø§Øª Ø§Ù„Ø±Ø³Ù„. ÙŠØªÙ… ØªØØ¯ÙŠØ¯ Ø§Ù„Ù‡ÙˆÙŠØ© Ù…Ù† Ø®Ù„Ø§Ù„ Ù…Ù‚Ø§Ø±Ù†Ø© Ø§Ù„ØªØ±Ø¬Ù…Ø© Ø§Ù„Ù‡ÙˆÙ„Ù†Ø¯ÙŠØ© Ù„Ù„Ù‚Ø±Ø¢Ù† Ø¨Ø§Ù„ØªØ±Ø¬Ù…Ø© Ø§Ù„Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ© Ù„Ù„Ù‚Ø±Ø¢Ù† Ø¨Ù‚Ù„Ù… ÙØ®Ø± Ø§Ù„Ø¯ÙŠÙ†ØŒ Ø²ÙŠÙ† Ø§Ù„Ø¯ÙŠÙ† ØÙ…ÙŠØ¯ (1962). ØªÙ… Ø§Ø³ØªØ®Ø¯Ø§Ù… ØªØÙ„ÙŠÙ„ Ø§Ù„Ù…ØØªÙˆÙ‰ Ù„ØªØÙ„ÙŠÙ„ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª. Ø¥Ù† Ø§Ù†ØØ±Ø§Ù Ø§Ù„ØªØ±Ø¬Ù…Ø© ÙÙŠ DHQ Ù†Ø§ØªØ¬ Ø¨Ø´ÙƒÙ„ Ø£ÙƒØ¨Ø± Ø¹Ù† Ø§Ù„ØªØ±Ø¬Ù…Ø© Ø§Ù„Ù…Ø¹Ø¬Ù…ÙŠØ© Ùˆ Ø£ÙŠØ¯ÙŠÙˆÙ„ÙˆØ¬ÙŠØ© Ø§Ù„Ù…ØªØ±Ø¬Ù… Ø§Ù„Ø°ÙŠ ÙŠØªØ±Ø¬Ù… Ø§Ù„Ù‚Ø±Ø¢Ù† Ø¨Ø´ÙƒÙ„ Ø¹Ù‚Ù„Ø§Ù†ÙŠ. Ø£Ø¸Ù‡Ø±Øª ØªØ±Ø¬Ù…Ø© Ø§Ù„Ù†Øµ Ø§Ù„Ù‚Ø±Ø¢Ù†ÙŠ Ø§Ù„Ù…Ø³ØªÙ†Ø¯Ø© Ø¥Ù„Ù‰ Ø£ÙŠØ¯ÙŠÙˆÙ„ÙˆØ¬ÙŠØ© Ø§Ù„Ù…ØªØ±Ø¬Ù… ØªØ¨Ø§ÙŠÙ†Ù‹Ø§ ÙÙŠ Ø§Ù„Ù…Ø¹Ù†Ù‰ Ù…Ø¹ Ø§Ù„Ù†Øµ Ø§Ù„Ø°ÙŠ ÙŠØ¯Ø¹Ù… Ø£ØØ¯Ø§Ø« Ø§Ù„Ø£Ù†Ø¨ÙŠØ§Ø¡. Ù‚Ø¯Ù… Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Â ÙˆØ¬Ù‡Ø© Ù†Ø¸Ø± Ø¬Ø¯ÙŠØ¯Ø© ÙÙŠ Ø§Ù„Ù†Ø¸Ø± ÙÙŠ Ø§Ù„Ø§Ù†ØØ±Ø§ÙØ§Øª ÙÙŠ ØªØ±Ø¬Ù…Ø© Ø§Ù„Ù†Øµ Ø§Ù„Ù‚Ø±Ø¢Ù†ÙŠØŒ Ù„Ø£Ù† ÙˆØ¬ÙˆØ¯ Ù…Ø±Ø§Ø¬Ø¹ Ù†ØµÙŠØ© ÙÙŠ Ø§Ù„ÙƒØªØ¨ Ø§Ù„Ù…Ù‚Ø¯Ø³Ø© Ø§Ù„Ø£Ø®Ø±Ù‰ ÙŠÙ…ÙƒÙ† Ø£Ù† ÙŠÙƒÙˆÙ† Ø¹Ø§Ù…Ù„Ø§Ù‹ ÙŠØ³Ø¨Ø¨ Ø§Ù†ØØ±Ø§ÙØ§Øª Ø§Ù„ØªØ±Ø¬Ù…Ø©.